Translation elongation: measurements and applications - Leslie Watkins; Mulin Li; Bin Wu (RNA Biology)
Translation converts genetic information in mRNAs into functional proteins. This process occurs in four major steps: initiation, elongation, termination and ribosome recycling; each of which profoundly impacts mRNA stability and protein yield. Over recent decades, regulatory mechanisms governing these aspects of translation have been identified. In this review, we focus on the elongation phase, reviewing the experimental methods used to measure elongation rates and discussing how the measurements shed light on the factors that regulate elongation and ultimately gene expression.